Food losses in international trade of agricultural commodities: A case study in Sri Lanka - Jeevika Weerahewa; Thushara Wickramaarchchi (Asia-Pacific Research and Training Network on Trade (ARTNeT), 2023)
Sri Lanka's development strategy has long emphasized enhancing trade competitiveness, with agriculture playing a significant role in its economy. This study addresses the critical yet often overlooked issue of food losses at the country's borders, which undermine its trade competitiveness. From 2016 to 2020, agricultural exports comprised about a quarter of Sri Lanka's total exports, while food imports accounted for around 13% of total imports. The research investigates the magnitude and causes of these border food losses and proposes strategies to mitigate them. Analysis using the Standard Compliance Analytics of UNIDO identified considerable rejections at entry and exit points. Stakeholder consultations indicated that these rejections primarily result from trading firms' inability to comply with complex regulatory and certification requirements. A lack of awareness among exporters about stringent standards in certain markets also contributes to these rejections. Stakeholders suggest strategies such as digitization, improved coordination between government agencies, and capacity building for government officials. The study recommends enhancing awareness among private agents about domestic and international regulations, improving the capacity of government officials, and developing infrastructure in the agricultural value chain, especially during grace periods following the introduction of new regulations, as well as prioritizing investments based on a cost-benefit analysis, considering both direct and indirect benefits of various options.
hdl:20.500.12870/6632
Keywords: Q17; F13; Q18; M48; 330; Stakeholder consultations; Food losses; Food security; GTAP